PENGARUH GOOD CORPORATE GOVERNANCE, LEVERAGE DAN AUDIT TENURE TERHADAP INTEGRITAS LAPORAN KEUANGAN (Studi Empiris Pada Perusahaan BUMN Yang Terdaftar Di Bursa Efek Indonesia Pada Tahun 2016-2018) - Zalfi M Harry Raudho; Hardi Hardi; Mela Fito Nanda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This research was examined the influence of the Independent Commissioner, Audit Committee, Managerial Ownership, Institutional Ownership, Leverage and Audit Tenure to Financial Statements Integrity. This research was conducted on 18 state-owned companies listed on the IDX in 2016-2018. This research design was quantitative where the data used in this research are secondary data obtained from the IDX website. The method used for sample selection is purposive sampling. The samples in this research were 18 companies. The results showed that the Independent Commissioner had no effect with a significance value of 0.398. The Audit Committee is proven to be influential with a significance value of 0.030. Managerial Ownership has no effect with a significance value of 0.071. Institutional Ownership has an effect with a significance value of 0.031. Leverage has an effect with a significance value of 0.004. Audit Tenure has an effect with a significance value of 0.047.Keywords : Financial Statements Integrity , Independent Commissioner, Audit Committee, Managerial Ownership, Institutional Ownership, Leverage and Audit Tenure,